Nurturing Children’s Socio-Emotional Development Through a Love-Based Arabic Curriculum: A Psychopedagogical Analysis - Murtadho, Mohamad Aris; Amrullah, Ahmad Fikri; Al Muiz, Mochamad Nasichin (Universitas Islam Negeri Raden Intan Lampung, 2026)
Early childhood Arabic language instruction often faces methodological challenges that cause learning anxiety, necessitating approaches that prioritize children's socio-emotional well-being. This study explores the implementation of a